Dropout in training courses of chemistry teachers in Brazil: Analysis of scientific articles (Revista Contexto & Educação, 2026)
This paper aims to verify, through scientometric analysis, how scientific articles approach the dropout in undergraduate chemistry courses in Brazil. Through the selection of articles in the CAPES Journal Portal (Coordination for the Improvement of Higher Education Personnel), it was observed that most publications were carried out from 2015 by public higher education institutions in the South region. It was also found that the authors do not publish much about the subject, and 35,3% of the papers do not discuss the used definition of dropout, making it difficult to fully understand the results. Finally, in the results of the publications, it was possible to relate dropout rates to factors such as students’ low affinity with the course, difficulty in reconciling work and study, problems with learning, high retention, curricular and socioeconomic problems. High dropout rates in the early years of the courses were mainly attributed to academic mobility. On the other hand, it was possible to identify the positive role of educational programs and quota policies, as well as the good social integration of students in the academic community, as aspects that can mitigate the phenomenon of dropout.
Keywords: Dropout; degree in chemistry; scientometrics